Employers most desirable attributes in early-career physiotherapists: a content analysis of job advertisements - R. McAleer; L. Hanson; A. Kenny (BMC, 2024)
Abstract Background Ensuring a sufficient, appropriately qualified health workforce is of global concern. Understanding the attributes that employers seek is critical in recruitment, retention, and educational design. In physiotherapy, there is a dearth of evidence on desirable attributes that employers seek from early-career physiotherapists. This study directly addresses this gap. The aims of this study were to identify the characteristics of the jobs advertised for early-career physiotherapists in Australia; determine which attributes were most desired when employing an early-career physiotherapist; and identify if there were differences in the attributes required based upon workplace location. Methods New graduate and early-career physiotherapy job advertisements were collected for six months from 1st October 2020 until 31st March 2021 from SEEK.com.au, a large online employment marketplace that operates across ten countries in the Asia Pacific and Latin America. Job advertisements needed to specify new graduate or early-career physiotherapist eligibility and be located within Australia. Data extraction were completed using QuestionPro®. The Modified Monash Model was used to classify rurality of job location. Job advertisements were analysed descriptively and using content analysis to identify attributes. Results The search yielded 578 job advertisements with the greatest number collected in October 2020 (25.3%). Of the advertisements, 428 (74.0%) were in metropolitan locations (Modified Monash 1), 47 (8.1%) were in regional (Modified Monash 2), 99 (17.1%) were in rural locations (Modified Monash 3-5), and 4 (0.8%) were in remote locations (Modified Monash 6-7). Most roles were in private practice (63.3%) or aged care (21.7%). The top five attributes requested by employers were client focus, communication and interpersonal skills, team player, willingness to learn, and being able to build rapport, relationships, and networks. Academic results, resilience, and empathy were the least requested attributes. Differences in requested employability attributes increased with rurality. Conclusions This study addresses the current knowledge about attributes sought by employers for early-career physiotherapists. The most prevalent attributes requested were client focus and communication and interpersonal skills. This exploration of attributes can help to better prepare graduates for their first roles, align expectations, and increase understanding of priorities for entry level university programs, as well as identify priorities for support during transition to practice. Desired attributes should be clearly defined by employers in recruitment and retention processes.